Complex I reductions in the nucleus basalis of Meynert in Lewy body dementia: the role of Lewy bodies - Christopher Hatton (9107257) (2020)
Neurons of the nucleus basalis of Meynert (nbM) are vulnerable to Lewy body formation and neuronal loss, which is thought to underlie cognitive dysfunction in Lewy body dementia (LBD). There is continued debate about whether Lewy bodies exert a neurodegenerative effect by affecting mitochondria, or whether they represent a protective mechanism. Therefore, the present study sought to determine whether the nbM is subject to mitochondrial dysfunctional in LBD and the association of Lewy body formation with such changes. Post-mortem nbM tissue was stained for Complex I or IV and quantitated relative to porin with immunofluorescence using confocal microscopy of individual cells from LBD (303 neurons, 8 cases), control (362 neurons, 8 cases) and asymptomatic incidental LBD (iLBD) cases (99 neurons, 2 cases). Additionally, α-synuclein, tau and amyloid-β pathology were analysed using quantitative immunohistochemistry, and respiratory chain markers were compared in cells with Lewy bodies (N = 134) and unaffected cells (N = 272). The expression of Complex I normalised to mitochondrial mass was significantly lower in LBD compared to control and iLBD cases and this was unrelated to local neuropathological burdens but trended toward a relationship with neuronal loss. Furthermore, Complex I expression was higher in cells with Lewy bodies compared to adjacent cells without α-synuclein aggregates. These findings suggest that Complex I deficits in the nbM occur in symptomatic LBD cases and may relate to neuronal loss, but that contrary to the view that Lewy body formation underlies neuronal dysfunction and damage in LBD, Lewy bodies are associated with higher Complex I expression than neurons without Lewy bodies. One could speculate that Lewy bodies may provide a mechanism to encapsulate damaged mitochondria and/or α-synuclein oligomers, thus protecting neurons from their cytotoxic effects. Other Information Published in: Acta Neuropathologica Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s40478-020-00985-8